Root canal treatment of a blunderbuss canal in the maxillary lateral incisor with dens invaginatus with apical plug application: a case report - Natsir, Nurhayaty; Siampa, Febrianty Alexes; Nugroh, Juni Jekti; Trilaksana, Aries Chandra; Dwiandhany, Wahyuni Suci; Hikmah, Noor; Rovani, Christine Anastasia (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2024)
ABSTRACTIntroduction: The incidence of anterior dental trauma in young adults is high. The impact of this has been previously reported that pulp necrosis occurs in 50% of young fixed anterior teeth so that the process of apex formation is disrupted and in some cases can cause a blunderbuss shape at the tooth root apex. Root canal treatment of blunderbuss teeth accompanied by dens invaginatus poses a challenge for a dentist. Aims of this case report to explain successful root canal treatment of a blunderbuss canal in the maxillary lateral incisor with dens invaginatus with apical plug application using MTA followed by esthetic rehabilitation. Case report: A 25-year-old female presented to RSKGM with a complaint of pain and swelling of the gingiva. History of trauma at the age of the patient was 10 years old without treatment. Clinical examination revealed a complete crown with dens invaginatus. Radiographic examination showed a periapical lesion and an open apex blunderbuss shape. Treatment performed was treatment with an apical plug using MTA and restoration using a peg crown. Shape root canal with a blunderbuss is an open apex root canal with the root apex diameter greater than the coronal diameter, hence requiring adequate material to form a cap over the root apex (apical plug). It has been reported that MTA is an apical plug material that has good sealing ability, biocompatibility, bacteriostatic activity and the ability to regenerate periradicular tissues. Conclusion:  Root canal  treatment of a blunderbuss canal in the maxillary lateral incisor with dens invaginatus with apical plug application of MTA material as apical plug is an effective method.Keywordapical plug, blunderbuss canal, dens invaginatus, mineral trioxide aggregatePerawatan saluran akar blunderbuss gigi insicivus lateral rahang atas dengan dens invaginatus dengan aplikasi apical plug: laporan kasusABSTRAKPendahuluan: Insidensi trauma gigi anterior pada pasien usia dewasa muda cukup tinggi. Dampak dari hal ini telah dilaporkan sebelumnya bahwa terjadi nekrosis pulpa pada 50% gigi anterior tetap muda sehingga proses pembentukan apeks terganggu dan pada beberapa kasus dapat menyebabkan bentuk blunderbuss pada apeks akar gigi. Perawatan saluran akar gigi blunderbuss yang disertai dengan dens invaginatus menimbulkan tantangan tersendiri bagi seorang dokter gigi. Tujuan laporan kasus ini melaporkan keberhasilan perawatan saluran akar gigi blunderbuss pada gigi insisivus lateral rahang atas dengan dens invaginatus dengan aplikasi apical plug menggunakan MTA yang dilanjutkan dengan rehabilitasi estetik. Laporan kasus: Seorang perempuan, 25 tahun datang ke RSKGM dengan keluhan nyeri dan pembengkakan pada gingiva. Riwayat trauma pada saat usia pasien 10 tahun tanpa dilakukan perawatan. Pada pemeriksaan klinis terlihat mahkota lengkap dengan dens invaginatus. Pemeriksaan radiografi menunjukkan lesi periapikal dan apeks terbuka berbentuk blunderbuss. Perawatan yang dilakukan adalah perawatan dengan apical plug menggunakan MTA dan restorasi menggunakan mahkota pasak. Bentuk saluran akar dengan blunderbuss adalah saluran akar apeks terbuka dengan diameter apeks akar lebih besar dari diameter koronal, oleh karena itu membutuhkan bahan yang adekuat untuk membentuk menutup ujung apeks akar (apical plug). Telah dilaporkan bahwa MTA adalah bahan apikal plug yang memiliki kemampuan sealing yang baik, biokompatibel, aktivitas bakteriostatik dan kemampuan meregenerasi jaringan periradikular. Simpulan: Perawatan saluran akar blunderbuss pada gigi insisivus lateral rahang atas dengan dens invaginatus dengan pengaplikasian apical plug bahan MTA sebagai apical plug merupakan metode yang efektif.Kata kunciapical plug, blunderbuss canal, dens invaginatus, mineral trioxide agregat